Digital marketing integrating strategy and tactics with values - Kaufman, Ira Morton, 1947- (Routledge, Taylor & Francis Group, 2015)
"Digital Marketing is an easy-to-understand guidebook that helps the reader to adopt a digital mindset, incorporate digital trends strategically, and integrate the most effective digital tools with core values to attain a competitive advantage"-- Provided by publisher.